Feeding styles and child weight status among recent immigrant mother-child dyads. - Tovar, Alison.; Hennessy, Erin.; Pirie, Alex.; Must, Aviva.; Gute, David M.; Hyatt, Raymond R.; Kamins, Christina Luongo.; Hughes, Sheryl O.; Boulos, Rebecca.; Sliwa, Sarah.; Galvão, Heloisa.; Economos, Christina D. (2016)
Background: Research has shown that parental feeding styles may influence children's food consumption, energy intake, and ultimately, weight status. We examine this relationship, among recent immigrants to the US. Given that immigrant parents and children are at greater risk for becoming overweight/obese with increased time in the US, identification of risk factors for weight gain is critical.; Keywords: Feeding styles, Children, Obesity, Immigrants.; Springer Open.